Effect of high-intensity pulse irradiation with linear polarized near-infrared rays on muscle tone in patients with cerebrovascular disease: a randomized controlled trial - Usuda, Shigeru; Takeuchi, Nobuyuki; Shimonishi, Yuko; Takezako, Nobuhiro (Journal of Physical Therapy Science, 2015)
[Purpose] This study evaluated effects of a high-intensity linear polarized near-infrared ray irradiation for mitigation of muscle hypertonia. [Subjects] The subjects were 20 patients with cerebrovascular disease. [Methods] Subjects were randomly allocated to an intervention or control group. The intervention group received irradiation of the triceps surae. Passive range of motion and passive resistive joint torque of ankle dorsiflexion were measured before and after the intervention in knee extended and flexed positions. [Results] In the knee extended position, the mean changes in passive range of motion were 2.70° and −0.50° in the intervention and control groups, respectively, and the mean changes in passive resistive joint torque were −1.42 and −0.26 N·m in the intervention and control groups, respectively. In the knee flexed position, the mean changes in passive range of motion were 3.70° and 0.70° in the intervention and control groups, respectively, and the mean changes in passive resistive joint torque were −2.38 and −0.31 N·m in the intervention and control groups, respectively. In both knee positions, the mean changes in the two indices were greater in the intervention group than in the control group. [Conclusion] High-intensity linear polarized near-infrared ray irradiation increases passive range of motion and decreases passive resistive joint torque.